Slack regulation compliance in the Mediterranean fisheries: a paradigm from the Greek Aegean Sea demersal trawl fishery, modelling discard ogives. (5th November 2012) - Damalas, D.; Vassilopoulou, V.
Abstract Annual discard ogives were estimated using generalised additive models (GAMs) for seven demersal fish species (or taxa) and deep‐water rose shrimp, Parapenaeus longirostris (Lucas). Analysis was based on data collected on board commercial bottom trawlers in the central Aegean Sea from 1995 to 2008. Length of specimens and fishing depth (along with year) were the variables that had the most profound effect on the proportion of fish discarded. Compliance with the established minimum catch size of marine organisms (MS) was very low, a fact attributed to the low selectivity of currently used mesh sizes, the market demand for undersized fish, as well as the low control and enforcement effort.